2016
DOI: 10.1039/c6ta06262h
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput computational screening of 137953 metal–organic frameworks for membrane separation of a CO2/N2/CH4 mixture

Abstract: A computational study is reported to high-throughput screen 137953 MOFs for a single-step membrane separation of a CO2/N2/CH4 mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 36 publications
5
82
0
Order By: Relevance
“…Since the GCMC+EMD approach is expected to give more accurate predictions at low pressure, we also calculated the permselectivities at infinite dilution using the GCMC+EMD method. This is a widely used approach for large‐scale screening studies . The popularity of the calculation of permselectivities at infinite dilution in large‐screening studies is due to the relatively short time required for computing the adsorption and diffusion selectivities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the GCMC+EMD approach is expected to give more accurate predictions at low pressure, we also calculated the permselectivities at infinite dilution using the GCMC+EMD method. This is a widely used approach for large‐scale screening studies . The popularity of the calculation of permselectivities at infinite dilution in large‐screening studies is due to the relatively short time required for computing the adsorption and diffusion selectivities.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, there have been only a few NEMD simulations of permeation of mixtures with three or more components . Furthermore, there are only a small number of studies which used the GCMC+EMD method to simulate separation of mixtures with three or more components . A robust molecular simulation approach for predicting the separation performance of membranes for multi‐component mixtures can be a powerful tool for predicting the selectivity of membrane materials for a specific multi‐component separation, as well as for understanding the complex transport phenomena of mixtures through porous membranes.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that most of the top 30 MOFs contain lanthanides. The same group screened 137953 hypothetical MOFs generated from the libraries of metals and organic linkers for membrane-based natural gas purification [57]. Twenty-four MOFs were prescreened for CO 2 /CH 4 and N 2 /CH 4 separations.…”
Section: Porous Materials Screeningmentioning
confidence: 99%
“…Jiang's group (Qiao et al, 2016a) used the CoRE MOF database to study both adsorption-based and membrane-based CO2/N2 and CO2/CH4 separations using molecular simulations. The same group also screened the hMOF database using combination of GCMC and MD simulations for membrane-based CO2 separation (Qiao et al, 2016b). Adsorption and diffusion data of gas mixtures are required to assess potential of the MOFs because gases naturally exist as mixtures in separation processes.…”
Section: Large-scale Screening Of Mofsmentioning
confidence: 99%
“…Molecular simulations were recently performed to screen 55,163 hMOFs for CO2/H2 separation and a genetic algorithm including optimization methods was used to identify the optimum physical properties of hMOFs which showed the highest separation performance . The limiting pore diameter and pore size distribution were reported as the key factors that affect CO2 permeation of hMOF membranes (Qiao et al, 2016b).…”
Section: Large-scale Screening Of Mofsmentioning
confidence: 99%